Study and Characterization of a Mineral Belayed Material: Case Tiles Coated - TOUKOUROU, CHAKIROU A.; FAGLA, FANOU ZINSOU BENOÎT; BELLO, Sobour (My University, 2015)
The study of water absorption and mechanical strength of the belayed coupled with normative provisions that enable the selection of tiles coated granites are suitable for both internal and external coatings on our premises and 20% rate coarse sand, the bi layers have good three-point flexural strength and compression; and a normal water absorption rate .They therefore can in these circumstances be used for coating. Standardized tests on sand and evaluation of mechanical characteristics of specimens (three-point bending strength and compression strength) by the three-point bending tests and compression are between the other methods. Indeed, the sample with coarse sand rate of 20% has a three-point flexural strength equal to 9,875MPa. The test results by 3 points bending method was used to assess the rate at 5.27% of uncertainty and stress fractures samples, As for compression, compressive strength of the specimens at first decreases with the assay (20% to 40%) in coarse sand. Then, they oscillate as coarse sand rate increasesfinally, the water absorption stimulates it decreases gradually as the coarse sand rate decreases with the exception of the 5050 sample.
Keywords: two-layer; water absorption; mechanical resistance.